KOTA TROPIS HEMAT ENERGI: MENUJU KOTA YANG BERKELANJUTAN DI INDONESIA - Tri Harso Karyono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Modern life and modern technology require vast use of energy. The use ofenergy in the cities has been dramatically escalated within the last decades. Since most of energy consumed by people live in urban areas is from the non-renewable resources like fossil fuels, we will certainly face problems of energy crisis and global warming to sustain our cities livable in the future. Due to the moderate prevailing climate conditions, which are close to the comfort temperature, less energy will be required to modify indoor temperature suitable for human indoor activities. Since the dependency to the energy is small, people in the humid tropic may have better chances to sustain their cities livable in the future. However, most of Indonesian cities are designed in such away with little consideration to some important design factors as climate, environment, energy, green transportation and an adequate infra structure, like urban drainage. In return, many cities are nothealthy and convinience to be lived for and are not in line with the sustainable design approach. This article provides some discussion on how tropical cities in Indonesia must be planned and designed toward sustainable built environment. Energy as the main role in sustaining our built environment is taken as a priority here to be considered in designing our humid tropical cities of Indonesia. This is in order to achieve sustainable living environment for our future generation and us.